Musik Langgam Jawa dalam Upaya Pemenuhan Kebutuhan Tidur Lansia - Nursalam Nursalam; Joni Haryanto; Retno Indarwati; Erna Dwi Wahyuni (Jurnal Ners, 2007)
Introduction: Quality and quantity of sleep dissorder are the commonest problems that faced by elderly. These problems can increase activity of sympathetic nerve and muscle stress. Javanese traditional music is one of the method to increase the fulfillment of the need of sleep. The objective of this study was to analyze the effect of Javanese traditional music on the fulfillment of the need of sleep in elderly. Method: Design of this study was a pre experimental design. The population was elderly with sleep disorders in Panti Sosial Tresna Werdha Blitar. There were 12 respondents which recruited by using purposive sampling who met to the inclusion criteria. The independent variable of this study was the Javanese traditional music and the dependent variable was the fulfillment of sleep in elderly. Data were collected by using structured questionnaire and biophysiological measurement and then analyzed by using Wilcoxon Signed Rank Test and Paired t-Test with level of significance α≤0.05. Result: The result showed that there was an effect of Javanese traditional music on quality of sleep (p=0.001), had an effect to increase the duration of sleep (p=0.00001), beside that it could reduce heart rate (p=0.001) and respiratory rate (p=0.00001). However, Javanese traditional music did not had significant effect to reduce sistolic blood pressure (p=0,104) and diastolic blood pressure (p=0339). Discussion: Conclution: Javanese traditional music had significant effect on the fulfillment of the need of sleep in elderly. Further research should measure the effect of Javanese traditional music on the fulfillment of the need of sleep with the rate of melatonin and EEG (Electro Encephalo Graphy).